Analysis of student scientific literacy: study on learning using ethnoscience integrated science teaching materials based on guided inquiry - Sakila Wati; Agil Al Idrus; Abdul Syukur (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
There are still few teachers who develop their teaching materials independently. There is also no continuity in science learning between scientific knowledge with real-life problems and local wisdom. As a result, learning is less meaningful, and students' scientific literacy skills remain low. This study aims to develop ethnoscience integrated science teaching materials based on guided inquiry that are appropriate and effective in improving students' scientific literacy. This study is development research that refers to the 4D development model. In addition to developing ethnoscience integrated science teaching materials based on guided inquiry, the researchers also developed syllabus, lesson plan, and students' scientific literacy instrument. The data collection technique used a validation sheet by three expert lecturers who are competent in their fields to measure the feasibility of the teaching materials. The scientific literacy instrument used multiple-choice questions. The data analysis technique used the validation percent index and the N-gain test to determine the increase in scientific literacy. Thi study obtained: 1) ethnoscience integrated science teaching materials (90); 2) syllabus (93); 3) lesson plan (90); and 4) scientific literacy instrument (90) with very valid and valid criteria; and revealed that 5) ethnoscience integrated science teaching materials can improve students' scientific literacy, as evidenced by the average score obtained by three schools with high improvement criteria. To summarize, this ethnoscience integrated science teaching materials based on guided inquiry are feasible and effective to be applied and implemented in learning to improve students' scientific literacy.